2020
DOI: 10.3390/su12156268
|View full text |Cite
|
Sign up to set email alerts
|

The Development and Validation of a Scale to Measure University Teachers’ Attitude towards Ethical Use of Information Technology for a Sustainable Education

Abstract: A self-administered measurement tool was developed and validated to provide data regarding ethical attitude of university teachers for a sustainable education. The research was based on several factors involved in forming attitudes towards the unethical information technology use. The sample: 334 Romanian teachers’ respondents who teach in the higher education system contributed to this research. A successions of factor analyses and structural equation modeling showed that a second-order model is a good fit fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 69 publications
(112 reference statements)
4
26
0
Order By: Relevance
“…(a) Guarantee that the information obtained through the analysis and the different interpretations value the reality that is being measured. The first of the objectives (a) was achieved following a standardized procedure for the construction of this type of scales [6,19,[30][31][32][41][42][43]; which was included from developing preliminary versions (alpha versions), to obtaining a beta version that was subjected to a content analysis by a group of experts in educational technology. After applying the Likert-type scale of eight response options, the experts' report showed that almost all the items were written in a language appropriate to their recipients, that they met the objectives set out in their design and that they were assessed with the maximum score for its clarity of presentation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…(a) Guarantee that the information obtained through the analysis and the different interpretations value the reality that is being measured. The first of the objectives (a) was achieved following a standardized procedure for the construction of this type of scales [6,19,[30][31][32][41][42][43]; which was included from developing preliminary versions (alpha versions), to obtaining a beta version that was subjected to a content analysis by a group of experts in educational technology. After applying the Likert-type scale of eight response options, the experts' report showed that almost all the items were written in a language appropriate to their recipients, that they met the objectives set out in their design and that they were assessed with the maximum score for its clarity of presentation.…”
Section: Discussionmentioning
confidence: 99%
“…With this paper, it was expected to awaken the sustainable awareness of readers, as well as that of the researchers and educators of different educational levels in everything related to the eco-responsible use of technologies. This is an important aspect because the concept of sustainable education in Spain is not yet sufficiently established in the school curriculum (it is only included in a superficial way) and it is a very necessary question [18,19]. Until now, this term was seen as associated exclusively with the natural and the most basic concept of ecology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In early education, digital citizenship aims to build an ethical and empathic foundation for the experiences in the virtual world that children will have. The responsible ethical use of technology (Mâţă et al, 2020) becomes a requirement of today's society, so it is necessary to form this skill from an early age.…”
Section: Rules For the Optimal Use Of Technology By Parents At Preschool Agementioning
confidence: 99%